IMPLEMENTASI TEKNOLOGI MESIN INDUSTRIAL DOUGH MIXER UNTUK PENINGKATAN KAPASITAS PRODUKSI IKM BOLEN PISANG SEMARANG - Nugroho, Agung; Pandu Annanto, Gilar; Nurfa'izin, Syafa'ah (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Bolen Pisang Small and Medium Industry (IKM) Mrs. Ayu Genuk Semarang as a partner in community service activities has problems in expanding her business. The first obstacle is regarding limited production capacity because the production process is still carried out conventionally without machines. The next obstacle is products that still don't have a PIRT permit due to limited information from partners. Therefore, to overcome the first obstacle, an industrial dough mixer machine was designed to speed up production time, especially when making dough. The machine is designed based on the conditions of the partner's business premises with specifications of a stripping capacity of 2.5 kg - 3 kg with a 0.5 hp driving motor. Socialization regarding the procedure for applying for a PIRT permit and assistance with product preparation was also carried out so that partners could expand their marketing network to large shops. From the results of the evaluation carried out, the implementation of the industrial dough mixer machine can speed up the process of making dry dough by 62% and 66% for wet dough when compared to before using the machine